2009
DOI: 10.1063/1.3177007
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar transport in solution-deposited pentacene transistors enhanced by molecular engineering of device contacts

Abstract: We report ambipolar transport in bottom gold contact, pentacene field-effect transistors (FETs) fabricated by spin-coating and thermally converting its precursor on a benzocyclobutene/SiO2 gate dielectric with chemically modified source and drain electrodes. A wide range of aliphatic and aromatic self-assembled thiolate monolayers were used to derivatize the electrodes and all enhanced electron and hole currents, yet did not affect the observable thin film morphology. Hole and electron mobilities of 0.1–0.5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
1
26
0
1
Order By: Relevance
“…On the contrary, when the gate voltage was swept from positive to negative bias, significant hysteresis was observed. 18,19 In the supplemental information, 28 the full transfer characteristics for a representative ambipolar pentacene FET (L ¼ 200 lm and W ¼ 2 mm) with a continuous V GS sweep from À50 V to 50 V is shown. Measurements in the unipolar saturation regimes ensured the minimum effect of hysteresis on the extracted mobilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, when the gate voltage was swept from positive to negative bias, significant hysteresis was observed. 18,19 In the supplemental information, 28 the full transfer characteristics for a representative ambipolar pentacene FET (L ¼ 200 lm and W ¼ 2 mm) with a continuous V GS sweep from À50 V to 50 V is shown. Measurements in the unipolar saturation regimes ensured the minimum effect of hysteresis on the extracted mobilities.…”
Section: Resultsmentioning
confidence: 99%
“…18 SAM modification of electrodes improved both hole and electron currents. In our previous report, we demonstrated that in constant aspect ratio devices (W/L ¼ 15), both electron and hole currents increase with channel width.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Pentacene thin film transistors (TFTs) were fabricated in bottom-gate, bottom-contact configuration on a Kapton® substrate according to the method described in [18] and [19]. A schematic of the device is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…One of the best examples is the typical observation of unipolar transport in organic field‐effect transistors (OFETs) and therefore the classification of organic p‐ and n‐type materials. It is only recently that theoretical2 and experimental3–5 reports have shown that the intrinsic properties of organic semiconductors can support both electron and hole transport. Theoretical calculations have predicted that organic semiconductors such as pentacene and tetracene can be as good electron conductors as hole conductors.…”
Section: Mobility and Threshold Voltage For Fets In Different Geometriesmentioning
confidence: 99%